Exploring The Compatibility Between English Teacher Professional Competency And Students’ Motivation In EFL Learning Process At High Schools - Dewi, Yoffie Kharisma (LPPM Universitas PGRI Sumatera Barat, 2025)
This study investigates the relationship between English teachers' professional competency and student motivation in high schools in Tanjungpinang, Indonesia. Recognizing the critical role of teacher competence in influencing student engagement and learning outcomes, this research addresses a gap in understanding how different aspects of teacher effectiveness impact student motivation across various schools. The study aims to evaluate how teachers' pedagogical skills, competency perceptions, and classroom strategies affect students' attitudes towards learning English. Using a qualitative approach, data was collected through interviews with four English teachers and questionnaires completed by 127 students from SMKN 1 Tanjungpinang, SMKS Maitreyawira Tanjungpinang, SMAN 2 Tanjungpinang, and SMA Pelita Nusantara Tanjungpinang. Key findings reveal that while overall student motivation is high, significant variability exists in how teaching methods and teacher competency are perceived and their effect on motivation. Teachers at different schools employ varied strategies, impacting student engagement differently. The study highlights the need for targeted professional development to address inconsistencies and improve teaching effectiveness. The implications suggest enhancing teacher training programs and refining classroom practices to foster a more uniformly motivating learning environment. Future research should explore longitudinal effects of teacher competency on student outcomes and further investigate the interplay of external factors affecting motivation.